Management of postembolization pain in patients undergoing uterine artery embolization for symptomatic fibroids - Paszkowski, Tomasz; Radomański, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Postembolization pain constitutes an important clinical problem of iatrogenic origin in patients undergoing uterine artery embolization (UAE) for symptomatic fibroids. The aim of this study was to evaluate the influence of adjuvant analgesia with paracetamol on the dose of the opioid (morphine) administered by means of patient-controlled analgesia (PCA). The obtained results justify the following conclusions: 1. Pain after embolization of uterine arteries often requires the use of intensive and multi-drug treatment. 2. The use of opioid PCA together with IV paracetamol significantly reduces the morphine dose required by patients with acute postembolization pain syndrome.